Imigração alemã e construção dos templos religioso: as Igrejas Evangélicas de Confissão Luterana no Brasil, da Paróquia de Tapera/RS - Petry, Tábara Varissa (2020)
Understanding the process of replacing the churches built by the first German colonizers with masonry constructions during the 20th century is the main objective of this research. For this purpose, the Parish of the Evangelical Church of Lutheran Confessio n in Brazil (IECLB), located in the city of Tapera - in the state of Rio Grande do Sul, is used as a study source. It is part of the scope of the study to assess whether the principles of the modern period influenced this replacement. When setting up inter faces between the constructive styles and the narratives obtained through oral history, the transformations represented in the constructive system since its arrival in the region will be exposed; Then, from a historical and architectural perspective, a comparative analysis of the buildings will be made, seen both through the constructive, aesthetic methods and belonging to religious styles and their cultural characteristics, as through the adaptation of the groups in a new space and the process of mutations resulting from the historical context that comprises the proposed time frame. This research takes into account the factors and actions that influenced German Lutheran (im)migrants to make choices and assimilations of different practices and languages from those they brought to their memory. In order to analyze the current architecture of the protestant temples of these communities, it is necessary to follow a path, to know the precepts and guidelines of religion and the formation of cultural identity in the scope of little-known lands. To achieve this, initially, aspects of the history of Lutheranism, of the issues of emigration/ immigration/migration, their development process and the cultural and identity profile of the subjects in question will be presen ted. In the other chapters, the intention will be to work on the technical and stylistic architectural analysis of the case studied, which is eight communities in total. The collection of data on the formation of communities and the construction of churche s is acquired through oral sources, reports and documents, with photographs being an important resource for comparative analysis. Authors like Yi-Fu Tuan helps to understand the transition of architectural language and the uses of space, especially religious, which creates and consolidates a social unity through its surroundings. The methods and forms of construction are latent sources of identity representation, such as wooden constructions, which are characteristic of the (im)migratory process. More specifically, it will be noticed the transformation path present in the current architecture that shows us how historical, cultural and vernacular memory is sustained, remains or is forgotten among constructions of staggered joints. It will be concluded that, i n the study region, the contribution of the construction system in staggered joints is a (im)migratory symbol, and, however, a characteristic is verified not only to an ethnicity, but, rather, a constructive form typical of German, Italian and Polish (im)m igrations, which adapted a simple method to an abundant material from their new land and standardized it in buildings of different uses, creating an architectural similarity between, for example, churches and residential buildings. By the reason to its low cost, both in material and labor, and due to its simple forms, this construction system becomes popular in the countryside, having expanded until approximately the 1980s, a period in which wood becomes a high cost material.